Aspects of information literacy with regards to the use of legal resources : case study of third year undergraduate law students of the University of Cape Town, South Africa and University of Jos, Nigeria - Lawal, Victoria (Library and Information Studies Centre (LISC), 2014)
Includes bibliographical references (leaves 182-213).